Development Of Web-Based Managerial Supervision Model In Junior High Schools - Patola, Jayantry; Dwikurnaningsih, Yari (LPPM Universitas PGRI Sumatera Barat, 2024)
The objectives of this research are: 1).Provide an overview of the implementation of managerial supervision services at Mdpna Hyera. 2).Analyze the weaknesses of managerial supervision services at Mdona Hyera, 3).Develop a Web-based managerial supervision model for school supervisors and principals. This research is research that uses the research and development model developed by Borg and Gall up to the seventh stage. Data collection techniques use interview guidelines, observation, documentation studies and expert validation questionnaires and web user questionnaires. The data was validated using a questionnaire validation sheet and interview sheet. The data analysis technique uses the Miles and Huberman model (1984). The technique used is descriptive qualitative. This step includes stages of data reduction, accurate data presentation, and data verification. Research results: 1). An overview of the implementation of supervisory and principal managerial supervision services that have been carried out in Mdona Hyera, 2). Weaknesses of managerial supervision services for supervisors and school principals in Mdona Hyera, 3). A web-based managerial supervision model for school supervisors and principals along with a guidebook for using it.